Forensic driver identification considering an unknown suspect - Dološ, Klara; Meyer, Conrad; Attenberger, Andreas; Steinberger, Jessica (Zielona Góra: Uniwersytet Zielonogórski)
One major focus in forensics is the identification of individuals based on different kinds of evidence found at a crime scene and in the digital domain. Here, we assess the potential of using in-vehicle digital data to capture the natural driving behavior of individuals in order to identify them. We formulate a forensic scenario of a hit-and-run car accident with a known and an unknown suspect being the actual driver during the accident. Specific aims of this study are (i) to further develop a workflow for driver identification in digital forensics considering a scenario with an unknown suspect, and (ii) to assess the potential of one-class compared to multi-class classification for this task.
Keywords: natural driving behavior; digital biometry; OCC; CAN-BUS data; validation